Component‐Interaction Reinforced Quasi‐Solid Electrolyte with Multifunctionality for Flexible Li–O2 Battery with Superior Safety under Extreme Conditions. Issue 6 (11th January 2019) - Shu, Chaozhu; Long, Jianping; Dou, Shi‐Xue; Wang, Jiazhao
Abstract: High‐performance flexible lithium–oxygen (Li–O2 ) batteries with excellent safety and stability are urgently required due to the rapid development of flexible and wearable devices. Herein, based on an integrated solid‐state design by taking advantage of component‐interaction between poly(vinylidene fluoride‐ co ‐hexafluoropropylene) and nanofumed silica in polymer matrix, a stable quasi‐solid‐state electrolyte (PS‐QSE) for the Li–O2 battery is proposed. The as‐assembled Li–O2 battery containing the PS‐QSE exhibits effectively improved anodic reversibility (over 200 cycles, 850 h) and cycling stability of the battery (89 cycles, nearly 900 h). The improvement is attributed to the stability of the PS‐QSE (including electrochemical, chemical, and mechanical stability), as well as the effective protection of lithium anode from aggressive soluble intermediates generated in cathode. Furthermore, it is demonstrated that the interaction among the components plays a pivotal role in modulating the Li‐ion conducting mechanism in the as‐prepared PS‐QSE. Moreover, the pouch‐type PS‐QSE based Li–O2 battery also shows wonderful flexibility, tolerating various deformations thanks to its integrated solid‐state design. Furthermore, holes can be punched through the Li–O2 battery, and it can even be cut into any desired shape, demonstrating exceptional safety. Thus, this type of battery has the potential to meet the demands of tailorability and comformability in flexible and wearable electronics. Abstract : A quasi‐solid‐state electrolyte (PS‐QSE) for flexible lithium–oxygen (Li–O2 ) batteries is fabricated based on an integrated solid‐state design by taking advantage of the component‐interaction between poly(vinylidene fluoride‐ co ‐hexafluoropropylene) and nano‐fumed silica in polymer matrix. The PS‐QSE based Li–O2 battery shows excellent cycling stability and superior safety under extreme conditions due to the the effective protection of lithium anode and the stability of PS‐QSE.